KAJIAN PROSES DAN NILAI ESTETIK BATIK TULIS DI RUMAH “BATIK RATO WMS (WIRAUSAHAWAN MUDA SUMENEP)” KABUPATEN SUMENEP - Yulia Nurul Fatih; Agus Sudarmawan; I Gusti Ngurah Sura Ardana (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
The research that carried out in “Batik Rato WMS” house at sub-regency Sumenep is aimed to Describing aesthetic value in _Batik Tulis_ from “Batik Rato WMS” house. Batik Rato WMS is the batik from Sumenep, Madura-East Java. The subjects of this research are people who are resource persons and Batik Rato WMS craftsmen Jl. Dr. Soetomo, Lingkungan Delama, Pajagalan, Kota Sumenep, Kabupaten Sumenep, Jawa Timur 69416. This research was conducting by using a qualitative type with a descriptive approach. The research focused on the motifs and colors of Sumenep batik. The data in this study were obtained by observation, interviews, and documentation. The following research finding are, as follows: The process of batik making are preparation and process of making. The motifs and colors of Batik Rato WMS through Monroe Beardsley’s aesthetic approach have the value of three aesthetic elements, such as integrity, complexity and sincerity. (1) Unity is found in visual elements that are distilled based on the main motif, combined with guri’, as well as elements of local culture in Sumenep such as the winged horse, Keris Keraton, Kerapan Sape, Blarak and flowers with contrasting and bright colors. (2) The complexity shown in the number of ornaments in each sheet of cloth, which is arranged very finely and repeatedly in expressive way. The variations of the supporting ornaments are quite complicated, this is due to the effort to display the keris element on each sheet of batik cloth which is located on the sleeve as a characteristic of this batik. Batik Rato WMS coloring required time and accuracy in the coloring process with varied motifs and ornaments. (3) The element of earnestness in the motifs and colors found in the shape character of the distinctive motif so that it describes locality of the area and the large motif by considering the quality of the various properties that exist in the value/philosophy, which defined as tenacity, patience and perseverance. Keywords: Aesthetic value, motif, color, Batik Rato WMS